Inequality and the Economic Cycle: Disabled Employees' Experience of Work during the Great Recession in Britain. (26th November 2020) - Jones, Melanie; Hoque, Kim; Wass, Victoria; Bacon, Nick
Abstract: Using unique questions introduced into the 2011 British Workplace Employment Relations Study, a detailed matched employee–employer survey, this article compares disabled and non‐disabled employees' experience of the 2008–2009 recession to contribute a cyclical perspective on disability‐related disadvantage at work. We find that disabled employees are more likely to report recession‐induced changes to workload, work organization, wages and access to training, even after controlling for personal, job and workplace characteristics. There is limited evidence that workplace equality characteristics moderate these relationships to protect disabled employees. These findings have particular resonance in the context of the COVID‐19 recession.